Antibiofilm agents and implant-related infections in orthopaedics: where are we?. (1st April 2013) - Romanò, Carlo L; Toscano, Marco; Romanò, Delia; Drago, Lorenzo
<x xml:space="preserve">Abstract</x> Orthopaedics is currently the largest market of biomaterials worldwide and implant-related infections, although relatively rare, remain among the first reasons for joint arthroplasty and osteosynthesis failure. Bacteria start implant infection by adhering to biomaterials and producing biofilms, which represent a major reason for bacterial persistence, in spite of antibiotic treatment and host's defence. In the last two decades, a number of different antibiofilm agents have been studied and both in vitro and in vivo results appear now promising, even if their effective role in orthopaedics remains to be assessed. In this review, we introduce an original classification of antibiofilm agents, based on their mechanism of action and examine the available data concerning their possible application to orthopaedic implant-related infections. Molecules that interfere with biofilm production (biofilm prevention agents) include anti-adhesion compounds, quorum sensing inhibitors, non-steroideal anti-inflammatory drugs, and antimicrobial peptides; N-acetylcysteine and specific enzymes promise the greatest therapeutic possibilities by disrupting established biofilms (biofilm disrupting agents). The identification of antimicrobials able to bypass the biofilm barrier (biofilm bypassing agents), and antibiofilm vaccines are further strategies aimed to reduce the impact of biofilm-related infections, opening new pathways in controlling implant-related infections. However, this review shows that still insufficient knowledge is currently available as to regard the efficacy and safety of the investigated antibiofilm strategies to treat infection that involve bone tissue and biomaterials commonly implanted in orthopaedics, pointing out the need for further research in this promising field.